Implementation Of Standard Costs As A Support Of Production Cost Control Testing Samples Of Pt Goodyear Indonesia Laboratory - Handayani, Meldi; Mulyana Dali, Rahmat; Rasiman, Rasiman (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
Standard costs are costs that should be incurred to make one unit of product specified at the beginning of the period. Standard costs become a benchmark for controlling a company's production costs. The purpose of this study is to analyze using standard costs as an effort to support production cost control. This study uses a descriptive type of research with a quantitative approach. This research focuses on controlling production costs by analyzing the actual costs. Documentation interviews and field observations are data collection techniques used. The results of the research on testing production samples at the PT Goodyear Indonesia Laboratory illustrate that the standards applied have not been able to control the cost of testing production samples. The cause of this is data failure in the sample compound which makes repeated sample tests, so that there is an increase and increase in the use of raw materials and an increase in electricity usage. Companies should review the manufacture of compounds in order to be more detailed and thorough so that the goods produced do not fail when testing samples.